Glimpse into the US-china bilateral trade imbalance. - Chan, Hoi Ting. (2008)
This paper seeks to address the causes of global imbalances through the macroeconomic perspectives of elasticity and savings-investment theories. We concentrate on the US-China bilateral trade relations by investigating the determinants of the US-China bilateral trade balance and their respective current account balances. Using the error correction model, we found that relative income growth rates and investment are the more influential elements in contributing to the trade imbalance. The Unit Labour Cost (ULC) is introduced as a form of cost competitiveness under the elasticity approach, and our findings showed that it is a significant factor.